Neighborhood nucleus protopia accommodating spaces underneath the Tejgaon-Bijoy sarani link road flyover - Nawar, Aniqa (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2018.